Project based learning untuk Mengembangkan Karakter Profil Pelajar Pancasila Elemen Kreatifitas dan Bergotong Royong pada Pembelajaran Sejarah - Khodijah Rezhi; Erlina Wiyanarti; Yeni Kurniawati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Problems that generally occur in teenagers are a character that needs to be developed through school educational institutions. Development that focuses on the Pancasila character profile, elements of creativity and mutual cooperation, with the hope that students will become people with character, so that they can become civilized humans. In reality, obstacles to understanding in developing it both from teachers and students, as well as the role of parents also determine character. Project based learning requires in its application to create a project that must be done, then produce written work, drawings, etc. The aim of this research is to obtain a description related to Project based learning to develop the character profile of Pancasila students, elements of creativity and mutual cooperation in history learning. The research design in this research is a literature study, namely the source is from various written articles that are related to the theme of discussion. Project based learning is a teaching and learning method as a solution to be implemented, and can be used to develop the character of students so that they have positive moral qualities. Through Project based learning, we can develop the character profile of Pancasila students, taken from several elements, for example elements of creativity and mutual cooperation in history learning which can be used to teach history correctly, meaning that teachers are able to choose problem themes and are able to choose to apply contextual learning methods and approaches so that achieve goals by connecting the material in the textbook with the surrounding environment.